Surviving Incarceration : Inside Canadian Prisons - Ricciardelli, Rose, 1979- (Book collections on Project MUSE., 2014)
"Reveals the unnecessary and omnipresent violence in prisons, the heterogeneity of the prisoner population, and the realities that different prisoners navigate in order to survive."--Publishers website